THE ROLE OF ISLAM IN SOLVING THE SOCIAL CRIMES - Umar AlFaruq Abubakar (Pondok Pesantren Modern Islam Assalaam, 2017)
The aim of writing this paper is to show the role of Islam in handling social crimes in society. Particularly, Islam has special concern in seven social evils. It can be seen from the punishment of these seven social evils. The Punishment for the perpetrators of these 7 social evils is stated clearly in the Holy Qur’ an. The punishment will be conducted firmly to those perpetrators. Those seven social evils are adultery, accusing others commit adultery, stealing, carouse (consuming alcohol), hooliganism, apostasy, and the rebellion against the legitimate government. Islam offers a very strong effect to perpetrators of those seven social evils, so that the perpetrators will not repeat his crimes. It also prevents the crimes to occur repeatedly.